Port of Spain, Trinidad, W.I. - (:unkn) unknown (3-D Natural Color Production, 2010)
Description printed on the back of the postcard: “The Carribbean’s [sic] newest luxury hotel where guests descend from the grand lobby to their rooms with their private balcony overlooking Port-of-Spain and the sea. Picturesque gardens and pools, restaurants and bar entertainment echo the holiday mood of this festive island.” The Lady Young Road can be seen at top left. Postcard number SDK-1767.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Hotels--Trinidad and Tobago; [1980]; Scenic overlooks--Trinidad and Tobago; Trinidad and Tobago--Aerial views; Dwellings--Trinidad and Tobago; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Swimming pools--Trinidad and Tobago; Roads--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Hotel chains--Trinidad and Tobago